High thermal conductivity EP adhesive based on the GO/EP interface optimized by TDI. (18th February 2020) - Xu, Hang; Zhang, Xiaorui; Hu, Guangkai; Weng, Ling; Liu, Lizhu
Abstract : Graphene oxide (GO) was used as the filler to modify the epoxy resin (EP) adhesive, and the GO/EP interface was optimized by toluene diisocyanate (TDI) in order to improve the thermal conductivity and T peel strength performance of the adhesive. Through the characterization of the GO product, which was modified by TDI, TDI was grafted onto the surface of GO, and there were NCO groups remaining; thus the chemical bonds were built onto the interface which was non‐wetting between GO and EP. The results of the properties characterization of the adhesive indicated that the bonding properties were significantly enhanced, especially the T peel strength, which was up to 9.62 N/mm, which was contributed by the optimized GO/EP interface. The thermal conductivity of the adhesive increased to 0.624 W m −1 K −1, as the interface thermal resistance was reduced after the interface between GO/EP was optimized by TDI. The insulation performance of the adhesive was also improved, since the well‐dispersed GO formed a micro‐capacitance model in EP, and the surface of GO was covered by the EP so that the electronic paths were blocked by the formed chemical bonds.